REVIEW OF THE INFLUENCE OF SLUICE BOX SUPPORTING PARAMETERS ON RECOVERY RESULTS OF METAL MINERAL PROCESSING - Afroza Pratiwi; Edy Nursanto; Eddy Winarno (Jurnal Scientia, 2023)
This mineral processing aims to separate valuable minerals from their impurities using mechanical methods by utilizing the physical and chemical properties of the minerals. One of them is by using gravity concentration with a sluice box tool. It is known that to achieve the desired recovery, this tool requires supporting parameters for optimal recovery, including dimensions and materials, riffles, slopes, water discharge, and carpet types. The purpose of this paper is to determine whether several supporting parameters really affect the results of metal mineral processing with the limitation of the problem is the influence of supporting parameters in various previous research results. The results of the review show that the supporting parameters affect the processing results. In addition, the parameters also influence each other. If the results of these parameters are not accurate, the processing results will also be less than optimal and material sedimentation will occur.